Analisis Nilai-Nilai Pendidikan Islam yang Terkandung dalam Makna Tersirat Nadzam Alfiyah Ibnu Malik dan Aktualisasinya pada Konteks Pendidikan Islam Moderen - Hilyah Ashoumi; Izza Fatkhiyyaa Khunainatuz Z (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2020)
Islamic education at this time has a lot to follow the development of an increasingly modernity. Of course in this case there is a negative side that accompanies it. In this case, it takes a fortress so that Islamic education does not come out of its original purpose. Nadzam Alfiyyah Ibn Malik by Muhammad Jamaluddin bin ‘Abdullah bin Malik al-Andalusi, which contains the knowledge of Nahwu and Shorof, which were infused in 1002 nadzam, turned out to contain Islamic educational values hidden in each of their stanzas. If examined deeper will bring up the sciences relating to human social life in everyday. The problem that is discussed in this study is the values of Islamic education contained in the implied meaning of Nadzam Alfiyyah Ibn Malik and their actualization in the context of modern education. This research is library, with the source Nadzam Alfiyyah Ibn Malik. Data is collected from various literatures, using the synthesis-deductive method of philosophical approach, ta'wil and tafsir isy’ari. Values of Islamic education implicit in Nadzam Alfiyyah Ibn Malik consist the values of faith, worship and moral education, where these values can be actualized in the context of modern education, especially in important components of education.